An excess of emission in the dark cloud LDN 1111 with the arcminute microkelvin imager - Scaife, A.; Hurley-Walker, Natasha; Green, D.; Davies, M.; Grainge, K.; Hobson, M.; Lasenby, A.; López-Caniego, M.; Pooley, G.; Saunders, R.; Scott, P.; Titterington, D.; et al. (Wiley-Blackwell Publishing Ltd., 2009)
We present observations of the Lynds' dark nebula LDN 1111 made at microwave frequencies between 14.6 and 17.2 GHz with the Arcminute Microkelvin Imager. We find emission in this frequency band in excess of a thermal free-free spectrum extrapolated from data at 1.4 GHz with matched u? coverage. This excess is >15s above the predicted emission. We fit the measured spectrum using the spinning dust model of Draine & Lazarian and find the best-fitting model parameters agree well with those derived from the Scuba data for this object by Visser, Richer & Chandler. © 2009 The Authors. Journal compilation © 2009 RAS.